Postoperative complications of combined phacoemulsification and pars plana vitrectomy in diabetic retinopathy patients - Gershoni, Assaf; Barayev, Edward; Jbara, Doha; Hadayer, Amir; Axer-Siegel, Ruth; Dotan, Assaf; Gal-Or, Orly; Tuuminen, Raimo; Ehrlich, Rita (Frontiers in Medicine, 2022)
Purpose: To compare intra- and postoperative complications in combined phacoemulsification and pars plana vitrectomy surgeries performed in patients with non-proliferative diabetic retinopathy (NPDR) versus proliferative diabetic retinopathy (PDR). Methods: Retrospective, case series of patients with diabetic retinopathy who underwent combined phaco-vitrectomy surgery between 2008 and 2017. We compared intraoperative complications including posterior capsular rupture and retinal tear, and postoperative complications including corneal edema, cystoid macular edema (CME), epiretinal membrane (ERM), neovascular glaucoma and persistent inflammation. Results: A total of 104 eyes from 104 patients were included in this study. 24 eyes (23.1%) were categorized as NPDR and 80 eyes (76.9%) as PDR. The most common indications for surgery in the NPDR group were ERM (67%) and rhegmatogenous retinal detachment (12.5%), while in the PDR group, vitreous hemorrhage (56%) and tractional retinal detachment (19%). The most common complication was CME (29% in NPDR and 26% in PDR, p=0.778). There were no statistically significant differences in intra- and postoperative complication rates between the NPDR and PDR groups, even after adjusting for confounders; patient age at surgery and indication for surgery. Retinal tears were the most common intraoperative complication in both groups, and CME was the most common post-operative one. Conclusion: Combined phaco-vitrectomy in PDR patients is a safe procedure, with relatively minimal risk for major complications. Nevertheless, new-onset CME was found in about a quarter of patients in both groups. Intraoperative anti-VEGF or steroid administration, and intense postoperative anti-inflammatory medication and follow-up should be regarded in phaco-vitrectomy regardless of DR level.